A study of some immunological features in aborted women infected with Toxoplasma gondii and Cytomegalovirus in Hilla city - Samah Ahmed Kadum; Alaa Fahim Abbas (Al-Qadisiyah Journal of Pure Science, 2017)
This study was conducted to determine the role of T.gondii and CMV in cases of abortion in pregnant women and detect the possible association between the two infections. The occurrence of two pathogens in relation to the age has been studied. The infections reaching peak in the age group (25-29) years old .We found that the highest prevalence of Toxoplasmosis and CMV infection recorded for women in the first trimester of pregnancy. Sera and placental biopsies were collected from aborted and controlled women. Enzyme linked immunosorbent assay (ELISA) were used to assess the presence of specific antibodies against T.gondii and CMV in addition to the estimation of the concentration of INF-Î³ at systemic and mucosal levels to determine the humoral and cellular immunity. T.gondii and CMV infections and the synergism infections between two organisms induce both humoral and cellular immune responses both at mucosal and systemic levels.